Sharing economy: a new insight / Azyyati Anuar, Daing Maruak Sadek and Hafizah Hammad Ahmad Khan - Anuar, Azyyati; Sadek, Daing Maruak; Ahmad Khan, Hafizah Hammad (Universiti Teknologi MARA, Kedah, 2022)
The sharing economy refers to an economic model that promotes the exchange of goods and services by utilizing the digital platform. The concept of the "sharing economy" has seen significant growth in recent years and is now impacting various aspects of today's socioeconomic system (Mondal & Samaddar, 2020). According to the report of Segaran (2020), with 650 million people and around USD 3 trillion combined Gross Domestic Product (GDP) in Southeast Asia (SEA), the sharing economy is anticipated to expand to meet the needs of increasingly discerning consumers. Despite inconsistent regulatory responses across the Association of Southeast Asian Nations (ASEAN), the success of businesses such as Grab, Uber, and Airbnb shows that customers are eager to engage in the sharing economy. It appeals to consumers due to its tendency to distribute goods and services almost on demand and its adaptable business models (Gilchrist, 2016). One of the well-known examples of the sharing economy is Airbnb. It is an online platform that lets property owners rent out their spaces to travelers looking for short or long-term accommodation. Furthermore, it serves as a payment gateway for both strangers with a reliable policy and small administration fees deducted from both parties. Airbnb also facilitates the availability of spaces between the host and the guest (Airbnb, 2008). Since its launch in 2007, Airbnb has created millions of listings in more than 192 countries and 34,000 cities across the world, affecting the traditional hotel industry while benefiting consumers and providers, influencing the travel industry to boost the nation's economic performance (Airbnb, 2008). Another example is the e-hailing services, such as Uber. It is a popular collaborative consumption model that competes with taxis as a traditional mode of transportation. Without having any physical assets or employees as their base of operation, Uber is an online transportation network company that manages a network of drivers and passengers in real-time. It offers ride-sharing options while generating income for new drivers and giving taxi customers another option (Aziz et al., 2017). Malaysia Digital Economy Corporation (MDEC) also focuses on accelerating digital economy growth, ensuring it is inclusive and rewarding for all. It specifically highlights the key drivers: empowering Malaysians with Digital Skills, enabling Digitally-Powered Businesses, and driving Digital Sector Investments. In particular, MDEC now dives into the prospects of sharing economy development in Malaysia in terms of (1) bridging the supply and demand gap by expediting longterm development and supporting ‘sharing economy’ platforms and (2) assisting businesses in implementing sharing economy services and solutions (MDEC, 2019). According to the director of MDEC, Mr. Darzy Norhalim, although the growth of the sharing economy has unquestionably benefited consumers due to its accessibility and convenience, it also led to conflicts with the government and other established business sectors. For example, the local taxi drivers have been protesting against the ride-sharing companies, and there have been questions on whether Airbnb and other home-sharing services will harm the hotel industry. To ensure a level playing field with traditional businesses, he claimed that the government is working to create a regulatory framework for sharing economy businesses. It can also be seen that the traditional industries are not harmed by sharing economy businesses; instead, it promotes the expansion of commercial opportunities throughout the economy, including the tourism and logistics industries. Hence, the demand for these services will keep rising as more people get involved in the relevant industries and indirectly will also benefit the established companies (Money, 2019).